Maternal and Neonatal Factors Affecting Bone Mineral Content of Indonesian Term Newborns - Wibowo, Tunjung; Nurani, Neti; Hastuti, Janatin; Anggraini, Alifah; Susilowati, Rina; Hakimi, Mohammad; Julia, Madarina; Van Weissenbruch, Mirjam (Frontiers in Pediatrics, 2021)
Background: Interactions between the genome and intrauterine environment can affect bone mineralization in newborns and even in adult life. Several studies show that intrauterine fetal bone mineralization or early postnatal bone condition influences the risk of osteoporosis in later life. Objectives: to determine bone mineral content (BMC) and factors that influence neonatal BMC in Indonesian term newborns. Subjects/Methods: A cross-sectional study was conducted in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. A total of 45 term, appropriate for gestational age (AGA) newborns were included in this study. BMC was assessed by dual-energy x-ray absorptiometry (DXA) in the first week of life. Weight (g), length (cm) and head circumference (cm) were measured at birth. Data on maternal characteristics were obtained from the maternal health records or reported by the mothers. Results: BMC measured in the present study (mean ± SD: 33.2  9.3 g) was lower than BMC of similar populations in developed countries. Multiple linear regression showed that birth weight, birth length, and gestational age had a positive association with BMC (p=0.048, 0.017, and <0.001, respectively), while maternal cigarette exposure had a negative association with BMC (p= 0.012). Male infants had significantly higher of BMC than female (p= 0.025). These determinants contribute to 55% variability of BMC. Conclusions: BMC in Indonesian term newborns is lower than populations in developed countries. Birth weight, length, gestational age, sex, and maternal cigarette exposure during pregnancy are significantly associated with BMC observed in Indonesian newborns.